Child ADHD and anxiety: Parent mental health literacy and information preferences. Issue 4 (6th March 2022) - Davidson, Dylan; Reynolds, Kristin; Theule, Jennifer; Feldgaier, Steven
Abstract: This research explored parents' mental health literacy (MHL) skills (i.e., recognizing symptoms and identifying effective help‐seeking strategies) for child attention‐deficit/hyperactivity disorder (ADHD) and anxiety, factors associated with their MHL, and preferences for receiving information about each disorder. N = 128 parents were recruited from community organizations to participate in an online survey. Parents were randomly assigned to read one vignette depicting a child with symptoms of ADHD or anxiety. They were asked to identify the depicted problem and rate the helpfulness of potential help‐seeking strategies (i.e., different health professionals and medications). They also completed measures of parental self‐efficacy and parenting stress and indicated information preferences for learning about symptoms and treatment. Parents scored just above the mid‐range on a measure of their MHL skills, with no significant difference between parents responding to the ADHD and anxiety vignettes. Stronger MHL was associated with being a mother, having personal, family, or friend‐related mental health experience, and stronger parental self‐efficacy. Parents were interested in receiving more information about child ADHD and anxiety via health provider or written format. Results are valuable for informing future MHL intervention efforts to educate parents about symptoms and treatment for common child mental health problems such as ADHD and anxiety.